Pemodelan dan Simulasi Arus Terobosan dalam Devais MOS - Khairurrijal Khairurrijal (Institut Teknologi Bandung, 2003)
1.5-2.0 nm thick gate oxides are required for the future metal-oxide-semiconductor field-effect transistors (MOSFETs) with 100-nm gate length. An accurate model is needed to predict the tunneling current through thinner gate oxides for the development of the transistor with the gate length less than 100 nm. The tunneling current is calculated on the basis of Harrison’s approach with the conditions that both sides of the oxide layer of he transistor have sharp interfaces and the BenDaniel-Duke effective mass approximation holds. Using the nonparabolic energy-momentum dispersion relation of he band gap of the gate oxide, the tuneling current through the gate oxide with thickness of 1.65-3.90 nm can be reproduced well by the model.